From Strain Ratio to Shear-Wave Elastography: Evolving Role of EUS in Liver Fibrosis Assessment - Kaldirim Armutcuoglu, Yasemin; Turan Gokce, Dilara (Turkish Journal of Gastroenterology, 2026)
Cite this article as: Armutcuoğlu Y. From strain ratio to shear-wave elastography: Evolving role of EUS in liver fibrosis assessment. Turk J Gastroenterol. Published online February 19, 2026. doi: 10.5152/tjg.2026.25663.